WAYS TO ACHIEVE THE PIONEERING TREND OF TOURISM ORGANIZATIONS BY ADOPTING THE DIMENSIONS OF BUZZ MARKETING - Asst. Prof. Dr. Alaa Abd Al Hussein Radhi (Scholar Express Journal, 2022)
The research aims to know the effect of associative marketing in achieving the pioneering orientation of tourism organizations and the extent to which tourism organizations adopt this concept. The research community represents the managers of tourist hotels, as well as the following statistical methods were relied upon: the arithmetic mean, standard deviation and regression coefficient in order to give a statistical description of the sample surveyed. A set of conclusions was the most important The hotels under study is working to achieve the pioneering orientation in its dimensions by working within the rules of ethical behavior A set of recommendations was the most important The hotel management invests in buzz marketing tools in order to create a sustainable mental image for customers of the organization and the services it provides by preparing opinion leaders to influence prospective customers and transfer the characteristics of those services to them, whether word-ofmouth or using social media.
Keywords: Buzz Marketing; Pioneering Trend; Tourism Organizations